Full genome characterization and evolutionary analysis of Banna virus isolated from Culicoides, mosquitoes and ticks in Yunnan, China - Yang, Zhenxing; He, Yuwen; Chen, Yiju; Meng, Jinxin; Li, Nan; Li, Susheng; Wang, Jinglin (Frontiers in Cellular and Infection Microbiology, 2023)
Banna virus (BAV), a potential pathogen that may cause human encephalitis, is the prototype species of genus Seadornaviru within the family Reoviridae, and has been isolated from a variety of blood-sucking insects and mammals in Asia. In this study, 13 strains BAV were isolated from Culicoides, Mosquitoes and Ticks collected in Yunnan, China. Their viral genome consisted of 12 segments of double-stranded RNA (dsRNA) by agarose gel electrophoresis analysis, with three distinct distribution patterns. The full genome sequences of the BAVs were determined by full-length amplification of complementary DNAs. Sequence analysis showed that Seg-5 of four strains (SJ_M46, SJ_M49, JC_M19-13 and JC_C24-13) has 435 bases nucleotide sequence insertions in their ORF compared to other BAVs, resulting in the length of Seg-5 up to 2128 nt. There are 34 bases sequence deletion in Seg-9 of 3 strains (WS_T06, MS_M166 and MS_M140). Comparison of the coding sequences of VP1, VP2, VP5, VP9 and VP12 of the 13 BAV strains, the results show that VP1, VP2 and VP12 are characterised by high levels of sequence conservation, while VP9 is highly variable, under great pressure to adapt and may be correlated with serotype. While also variable, VP5 appears to be under less adaptive pressure than VP9. Additionally, phylogenetic analysis indicates that the 13 BAV strains locate in the same evolutionary cluster as BAVs isolated from various blood-sucking insects, and are clustered according to geographical distribution. These results provide new insights into the genetic diversity and geographic distribution of members of the species BAV.